2020
DOI: 10.21203/rs.3.rs-31214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intention to Vaccinate Against the Novel 2019 Coronavirus Disease: The Role of Health Locus of Control and Religiosity

Abstract: The urgency to develop a vaccine against the 2019 coronavirus (COVID-19) has waxed stronger in speed, scale, and scope. However, wisdom dictates that we take a vantage position and start to examine the demographic predictors of COVID-19 vaccine hesitancy. The objective of this study was to examine the role of health locus of control (HLOC) in the relationship between religiosity and COVID-19 vaccination intention. In a cross-sectional survey (N=501), we found a significantly negative association between religi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…They are compatible with recent research showing that religiosity is negatively associated with trust in scientific COVID-19 research and positively associated with COVID-19-related conspiracy ideation (Freeman et al, 2020; Plohl & Musil, 2020). Not surprisingly, religiosity has been found to be negatively related to COVID-19 vaccination intention (Olagoke, Olagoke, & Hughes, 2020). Note that the present unreasonable behavior scale includes two items many conspiracy theorists would agree to (avoidance of 5G technology, protection by silver nanoparticles).…”
Section: Discussionmentioning
confidence: 99%
“…They are compatible with recent research showing that religiosity is negatively associated with trust in scientific COVID-19 research and positively associated with COVID-19-related conspiracy ideation (Freeman et al, 2020; Plohl & Musil, 2020). Not surprisingly, religiosity has been found to be negatively related to COVID-19 vaccination intention (Olagoke, Olagoke, & Hughes, 2020). Note that the present unreasonable behavior scale includes two items many conspiracy theorists would agree to (avoidance of 5G technology, protection by silver nanoparticles).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the fact that the regression analysis showed that more religious people were characterized by higher lockdown index scores than less religious people may seem surprising. One tentative explanation of this result is that religiosity is strongly positively correlated with trust in information obtained from informal sources (spiritual leaders, family and friends, and websites of religious organizations), which are not necessarily reliable and may contradict scientific data [42]. Thus, this tendency might have fueled people's faith in unverified information concerning the efficacy of various medications as prophylactics against the new coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, efforts to address vaccine hesitancy among populations should focus on providing accurate information, addressing misconceptions, and building trust in the safety and efficacy of vaccines within these communities. Collaborative initiatives with trusted religious leaders, community organizations, and healthcare providers who understand the cultural and religious nuances can be effective in addressing vaccine hesitancy among populations with diverse religious and cultural backgrounds [24,29].…”
Section: Discussionmentioning
confidence: 99%